Uncovering Regulators of Heterochromatin Mediated Silencing Using a Zebrafish Transgenic Reporter - Calvird, Audrey E.; Broniec, Morgan N.; Duval, Katherine L.; Higgs, Alysha N.; Arora, Vani; Ha, Lauren N.; Schouten, Erik B.; Crippen, Annabel R.; McGrail, Maura; Laue, Kathrin; Goll, Mary G. (Frontiers in Cell and Developmental Biology, 2022)
Heterochromatin formation and maintenance is critical for the repression of transcription from repetitive sequences. However, in vivo tools for monitoring heterochromatin mediated repression of repeats in the context of vertebrate development have been lacking. Here we demonstrate that a large concatemeric transgene integration containing the dsRed fluorescent reporter under the control of a ubiquitous promoter recapitulates molecular hallmarks of heterochromatic silencing, and that expression from the transgene array can be reactivated by depletion of known regulators of heterochromatin. We then use this reporter to identify a previously unappreciated role for the zebrafish NSD1 orthologs, Nsd1a and Nsd1b, in promoting heterochromatin mediated repression. Our results provide proof-principle that this transgenic reporter line can be used to rapidly identify genes with potential roles in heterochromatic silencing in the context of a live, vertebrate organism.